Hubungan Aktivitas Fisik Dengan Kadar Glukosa Darah Puasa Pada Wanita Dengan Lingkar Pinggang Di Atas 80 cm - Azarya Hananya Noritha; Yunus Elon (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
Lack of physical activity can cause a person to suffer from obesity, this condition if maintained will result in a high risk of heart and blood vessel disease and the outbreak of diabetes. The purpose of this study was to examine the relationship between physical activity and fasting blood sugar levels in women who have a waist circumference of more than 80 cm. This study uses a quantitative method with a cross-sectional design. A total of 30 female respondents were selected using the purposive sampling technique. Univariate and bivariate analyses were used to analyze subject data. Based on data analysis using SPSS, the majority of subjects (77%) had normal blood glucose levels, and 50% of subjects were in the obese category. Bivariate analysis showed no significant relationship between physical activity and fasting blood glucose levels p-value = >.05. In this study, it was found that physical activity did not have a significant effect on fasting blood glucose levels in women with a waist circumference above 80 cm. It is expected that women with a waist circumference above 80 cm can better maintain their lifestyle so that fasting blood glucose can be controlled and avoid diabetes.